Leucine-rich glioma inactivated 3: a novel keratinocyte-derived melanogenic cytokine in vitiligo patients - Farag,Azza Gaber Antar (2019)
Abstract: Background: In-vitro studies showed that Leucine-rich glioma inactivated 3 (LGI3) is a keratinocyte-derived cytokine that stimulates melanin synthesis and is increased after ultra violet B (UVB) irradiation. So, we postulated that LGI3 may be involved in vitiligo aetiopathogenesis and may participate in narrow band ultra violet B (NB-UVB) induced pigmentation in vitiligo. Objectives: To assess this hypothesis, lesional LGI3 immunohistochemical expression of vitiligo patients before and after NB-UVB phototherapy was studied, and its correlation with repigmentation was evaluated. Methods: Forty vitiligo patients and 20 age, sex, and skin phenotype-matched controls were enrolled. Patients were treated with NB-UVB thrice weekly for 12 weeks. VASI score was evaluated before and after NB-UVB sessions. For vitiligo patients, baseline LGI3 immunohistochemical staining was estimated, and compared to that of controls and to its post-treatment data in those patients. Results: Baseline LGI3 immunohistochemical studied parameters (expression, intensity, percentage and H score) were significantly lower in vitiligo cases than controls (p=0.003, 0.013, 0.001 and 0.001 respectively). After 12 weeks of NB-UVB phototherapy, these LGI3 immunohistochemical parameters were up-regulated and became comparable to that of controls (p >0.05 for all). There was a significant positive correlation between the improvement of both VASI score and LGI3 H score mean values (r=-0.349 , p=0.027). Study limitations: Small number of investigated subjects. Conclusions: Decreased LGI3 protein may play an active role in vitiligo pathogenesis and its up-regulation after NB-UVB phototherapy, may actively participate in NB-UVB photo-induced melanogenesis.